Challenges in Designing Smarter Mobile User Experiences - Romão, Teresa (Frontiers in ICT, 2016)
The ubiquitous use of smartphones has brought enormous changes to our everyday life. Many applications, that explore the ever-increasing capabilities of mobile devices, have been designed to make our life easier, facilitating the completion of numerous tasks, stimulating social relationships by connecting people in remote locations, promoting behaviour changes, and entertaining us. However, there are still many challenges to overcome when designing mobile user experiences that provide non-intrusive natural interfaces, as well as opportune interaction. Moreover, new smart mobile devices are generating additional expectations. This paper builds on the current use of mobile applications and reviews some of the challenges involved in creating smarter mobile user experiences.